FAMILY SUPPORT WITH THE HEALTH BEHAVIOR OF PULMONARY TUBERCULOSIS PATIENTS AT THE X SIDOARJO HEALTH CENTER - Meli Diana; Agus Sulistyowati; Mira Febrianti (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Tuberculosis is a very dangerous disease and can cause death. Many efforts have been made by the government to overcome this disease and have saved around 66 million lives since 2000. However, efforts to overcome this disease have been in vain due to the pandemic of COVID-19. Objectives: The aim of this research is to identify the relationship between family support and the health behavior of pulmonary tuberculosis sufferers. Methods: This research uses a cross-sectional approach using incidental sampling techniques. The sample in this study was 51 pulmonary tuberculosis patients at Community Health Center X who had undergone treatment for two to six months. Results: Based on the data obtained in this study, the majority of respondents with good family support had good health behavior, namely 56%. The analytical test used to determine the relationship in this research is the Spearman rank analysis test. The results of the Spearman analysis obtained a p-value of 0.001 Conclusion: it can be concluded that there is a significant relationship between family support and self-care for pulmonary TB clients (p-value <0.05), with a correlation coefficient showing a positive value of 0.442. This shows that the higher the family support for pulmonary tuberculosis sufferers, the better the implementation of health behavior by sufferers.